EDUCATIONAL PSYCHOLOGY IN CHILDREN IN JORDAN: UNDERSTANDING COGNITIVE, EMOTIONAL, AND SOCIAL DEVELOPMENT IN AN ARAB CONTEXT - Ahmad Bani Amer, Mohammad (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2025)
The field of educational psychology has gained significant attention over the years, particularly in the context of different cultural and educational settings. This paper explores the educational psychology of children in Jordan, highlighting the impact of cognitive, emotional, and social development within the unique cultural context of the Middle East. The study reviews various factors affecting children’s learning processes, including parental involvement, socio-economic status, cultural values, and the influence of the traditional educational system. It also delves into the role of teachers, the curriculum, and how these aspects interact to influence children’s academic and emotional development. Furthermore, the research addresses challenges children face in their learning journey, including socio-cultural barriers, mental health concerns, and the educational policies that shape the schooling system. Based on a thorough review of current research and existing data, this article provides a comprehensive analysis of the educational psychology of children in Jordan and how these insights can contribute to improving educational practices and policies in the region. Ultimately, it argues for a more inclusive, culturally sensitive approach to education that considers the cognitive, emotional, and social development of students in Jordan’s unique educational environment. The paper aims to contribute to the growing body of knowledge in educational psychology and offers recommendations for future research and intervention programs.